Parents' evaluation of the IDEFICS intervention: an analysis focussing on socio‐economic factors, child's weight status and intervention exposure. (December 2015) - Nicholls, S. G.; Pohlabeln, H.; De Bourdeaudhuij, I.; Chadjigeorgiou, C.; Gwozdz, W.; Hebestreit, A.; Lauria, F.; Lissner, L.; Molnár, D.; Santaliestra‐Pasías, A. M.; Veidebaum, T.; Williams, G.; et al.
Summary: Introduction: From April 2008 to August 2010 the Identification and prevention of Dietary‐ and lifestyle‐induced health EFfects In Children and infantS (IDEFICS) intervention aimed to encourage healthier diets, higher physical activity levels and lower stress levels among European children and their families. While the intervention was intended to improve children's health, we also wished to assess whether there were unwelcome aspects or negative side‐effects. Therefore all parents of children who participated in the IDEFICS intervention were asked for their views on different aspects of the intervention. Methods: A total of 10, 016 parents of children who participated in the IDEFICS survey and who were involved in the intervention were invited to complete a questionnaire on positive and negative impacts of the intervention. Responses to each of the statements were coded on a four point Likert‐type scale. Demographic data were collected as part of the baseline (T0 ) and first follow‐up (T1 ) surveys; intervention exposure data was also collected in the T1 follow‐up survey. Anthropometric data was collected in the same surveys, and child's weight status was assessed according to Cole and Lobstein. After initial review of the univariate statistics multilevel logistic regression was conducted to analyse the influence of socio‐economic factors, child's weight status and intervention exposure on parental responses. Results: In total 4, 997 responses were received. Approval rates were high, and few parents reported negative effects. Parents who reported higher levels of exposure to the intervention were more likely to approve of it and were also no more likely to notice negative aspects. Less‐educated and lower income parents were more likely to report that the intervention would make a lasting positive difference, but also more likely to report that the intervention had had negative effects. Parents of overweight and obese children were more likely to report negative effects – above all, that 'the intervention had made their child feel as if he/she was "fat" or "overweight."' Conclusion: While the results represent a broad endorsement of the IDEFICS intervention, they also suggest the importance of vigilance concerning the psychological effects of obesity interventions on overweight and obese children.